The role of mitochondrial K(ATP) channels in antiarrhythmic effects of ischaemic preconditioning in dogs - Vegh, Ágnes (2002)
1. In the canine a single brief (5 min) coronary artery occlusion protects the myocardium against the severe ventricular arrhythmias and reduces the ischaemic changes that result from a subsequent, more prolonged (25 min) occlusion. The main purpose of the present study was to examine whether mitochondrial K(ATP) channels are involved in this protection. 2. In chloralose-urethane anaesthetized dogs, preconditioning (PC) was induced by a single 5 min period occlusion of the left anterior descending (LAD) coronary artery, 20 min prior to a 25 min occlusion of the same artery. In some of these PC dogs 5-hydroxydecanoate (5-HD; 150 μg kg(−1) min(−1) by intracoronary infusion) was given over a period of 30 min either before, or after PC. In other dogs the mitochondrial K(ATP) channel opener diazoxide (1 mg kg(−1); i.c.) was given, either alone or in the presence of 5-HD. Control dogs (infused with saline) were simply subjected to a 25 min occlusion and reperfusion. 3. Compared to controls, both PC and diazoxide significantly reduced the number of ventricular premature beats (VPBs; 295±67 to 89±28 and 19±11, respectively; P<0.05), the number of episodes of ventricular tachycardia (VT; 8.3±4.2 to 1.6±0.9 and 0.2±0.1; P<0.05) and the incidences of VT (100 to 43 and 33%; P<0.05) and ventricular fibrilation (VF; 60 to 0 and 17%; P<0.05) during the 25 min occlusion of the LAD. Further, 43% of the PC dogs and 58% of the diazoxide treated dogs survived the combined ischaemia-reperfusion insult (cp. 0% in the controls; P<0.05). The protection afforded by PC and diazoxide was abolished by 5-HD, especially when it was given prior to the PC occlusion. In the presence of 5-HD, three out of 10 dogs fibrillated during the PC occlusion and another three dogs died following reperfusion. Furthermore, there were no survivors in this group from the prolonged ischaemia/reperfusion insult. 5-HD given after PC only attenuated the antiarrhythmic protection. 4. Opening of mitoK(ATP) channels prior to ischaemia by preconditioning and diazoxide protects the myocardium against ischaemia and reperfusion-induced arrhythmias. This protection is abolished if the opening of these channels is prevented by the prior administration of 5-HD but only attenuated if 5-HD is given after preconditioning. The results indicate that opening of mitoK(ATP) channels prior to ischaemia is mandatory for protection against ischaemia and reperfusion-induced arrhythmias.